The role of Ownership Expropriation on relationship between Climate Change Effort and Tax Avoidance: Evidence from Malaysia - Hui Wei, You (Universiti Malaysia Sarawak, 2015)
This study is to examine the relationship between tax avoidance, climate change efforts, firm size, growth, profitability, leverage and ownership expropriation in Malaysia during the sample periods from year 2008 to 2013. Based on the sample of 248 publicly listed in Bursa Malaysia for 6 year and the chosen company from the 6 industries which are consumer, construction, plantation, property, technology and trading. This result shows that the higher climate change effort disclosure of a company, the lower the tax avoidance or tax planning. The results find that the climate change effort is significantly negative relationship with the tax avoidance. The results of other independent variables are inconsistent relationship with the hypothesized. Additional the empirical result suggest that there is moderating effect of ownership expropriation on the relationship between of climate change efforts and tax avoidance. Meaning that the ownership expropriation involve positive or negative impact on the relationship between tax avoidance and climate change effort, regardless the ownership expropriation is high or low.